PATIENT REPORTED OUTCOMES ARE ASSOCIATED WITH ISOMETRIC STRENGTH DEFICITS EARLY AFTER ACL RECONSTRUCTION IN ADOLESCENTS. Issue 4 (28th April 2020) - Weaver, Adam; Macmillan, Lauren; Suprenant, Danielle; Giampetruzzi, Nicholas
Background: Quadriceps Femoris (QF) strength has been identified to impact patient reported function following ACL reconstruction (ACLR) at time of return to sport. Patients with higher subjective reports of knee function displayed greater QF symmetry. To our knowledge the relationship between patient reported outcomes and strength measurements have not been studied during the rehabilitation process in adolescent patients post ACLR. Hypothesis/Purpose: The purpose of this study was to examine the relationship of International Knee Documentation Committee subjective form (IKDC) and the Anterior Cruciate Ligament Return to Sport After Injury (ACL-RSI) scores to isometric QF strength at three months status post ACLR. Methods: A retrospective chart review was conducted on patients treated with ACLR between July 2017 and April 2019 at a single institution. Patients between 12 and 20 years of age that underwent ACLR and completed a three-month functional tests assessment were included in the study. Data was collected for IKDC and ACL-RSI scores, and isometric strength testing at 60° of knee flexion on the HUMAC isokinetic dynamometer (CSMI USA, Stoughton, MA). Pearson correlation was used to determine if there is an association between IKDC and isometric strength, and Spearman Correlation to determine if there is an association between ACL-RSI and isometric strength. Results: The cohort included 138 patients (68 females; 16.16±1.88) (97.31±16.12 post-op days) status post ACLR, with an average IKDC score of 69.73±13.19 and average ACL-RSI score of 60.08±24.19. Hamstring autografts were the most common reconstruction (n=80, 58%). The average QF peak torque was 71.30±28.98 ft-lbs and average isometric QF strength deficit was 31.07±23.85 percent. IKDC scores were positively associated with QF peak torque isometric strength (r=0.437, P=<.0001). ACL-RSI scores were also positively associated with peak torque QF isometric strength (r=0.284, P=.001) and negatively associated with QF strength deficit (r= -.279, P=<.002). Conclusion: IKDC and RSI were positively associated with QF isometric strength in adolescent patients three months status post ACLR. These finding suggest that QF strength impacts patients' reported function and psychological readiness to return to sport at this time point. Possible impact on rehabilitation includes implementing strategies to progress QF strength from three months status post to time of return to sport.